The Effect of Local-Ore Fertilizers and Planting Methods on the Acorn Root System (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
As a result of 3-year studies, it was revealed that in the Sultan cotton, the growth, development and productivity of plants when determining 15 and 30 t/ha of manure, the roots of plants develop intensively compared to the control plot, the fost and adsorption capacity of root systems increases, as a result of productivity of raw cotton increases by 11-12.3 c/ha. Any root is inextricably linked with the soil environment and factors and is the main determining organ in its formation. Along with Root absorption, various compounds, microflora and fauna beneficial substances are also allocated to the soil environment, participate in the formation of fertile, granular particles.